2002
DOI: 10.1016/s0002-9440(10)64244-7
|View full text |Cite
|
Sign up to set email alerts
|

α-Methylacyl-CoA Racemase: Expression Levels of this Novel Cancer Biomarker Depend on Tumor Differentiation

Abstract: alpha-Methylacyl-CoA racemase (AMACR) has previously been shown to be a highly sensitive marker for colorectal and clinically localized prostate cancer (PCa). However, AMACR expression was down-regulated at the transcript and protein level in hormone-refractory metastatic PCa, suggesting a hormone-dependent expression of AMACR. To further explore the hypothesis that AMACR is hormone regulated and plays a role in PCa progression AMACR protein expression was characterized in a broad range of PCa samples treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
126
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(137 citation statements)
references
References 24 publications
8
126
1
2
Order By: Relevance
“…There is some suggestion that the protein expression of P504S is related to the grade of the tumor with the highest expression in a tubular adenoma and decreased expression in high-grade tumors. 15 Since metastatic tumors are more likely to be high grade, the decreased expression of P504S in the metastatic colorectal carcinomas in our study is not surprising.…”
Section: Distinguishing Primary Ovarian From Metastatic S Logani Et Almentioning
confidence: 55%
See 2 more Smart Citations
“…There is some suggestion that the protein expression of P504S is related to the grade of the tumor with the highest expression in a tubular adenoma and decreased expression in high-grade tumors. 15 Since metastatic tumors are more likely to be high grade, the decreased expression of P504S in the metastatic colorectal carcinomas in our study is not surprising.…”
Section: Distinguishing Primary Ovarian From Metastatic S Logani Et Almentioning
confidence: 55%
“…16,32 The expression of this protein in cancer precursor lesions such as high-grade prostatic intraepithelial neoplasia and colorectal adenoma suggests that it has a role in early carcinogenesis. 15 The expression of this protein in ovarian carcinoma has not been formally studied and limited information is available on its expression profile in epithelial tumors of the ovary of different histologic subtypes. In this study, 32% of metastatic colonic adenocarcinomas to the ovary showed diffuse expression of P504S as compared to none of the primary ovarian tumors.…”
Section: Distinguishing Primary Ovarian From Metastatic S Logani Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with other studies we also confirmed the idea of using AMACR as a marker of progression as its expression was increased in advanced stages of the cancer. 24,25 The multiplex model, which was composed of all seven biomarkers including serum PSA, showed significantly good AUC (AUC ¼ 0.744). Further, as this model would not be cost-and labor-effective, three additional models were generated.…”
Section: -13mentioning
confidence: 99%
“…In spite of the availability of biomarkers for PCA, the basic molecular mechanisms regulating its development and progression are still very poorly understood (Nupponen and Visakorpi, 1999;Jiang et al, 2001;Kuefer et al, 2002;Rubin et al, 2002;Varambally et al, 2002;Yang et al, 2002). Recognition of the precursor lesions of PCA has become a primary focus in recent years.…”
Section: Introductionmentioning
confidence: 99%